The Impact of Personal Student Characteristics on Mathematics Achievement for Nontraditional Students in an Online Charter High School - Nathan Hawk; Kui Xie; Azita Manouchehri (Journal of Urban Mathematics Education)
The purpose of this study was to examine the relationship between student at-risk factors and mathematics achievement combining more adaptive personal student characteristics with risk factors in an online virtual-based learning environment. Further, this study examined how personal student characteristics, which are often amenable to change and intervention, both directlty predict and then moderate the relationship between risk and Algebra 1 achievement, controlling for student age and gender. Sixty-three Algebra 1 students in one were surveyed about perceptions of their self-efficacy and study management. Using multiple linear regression, results show that students’ domain-specific self-efficacy in mathematics contributed most to course grade among the hypothesized moderators while other hypothesized personal student characteristics (technology efficacy for online learning and time management) had negligible effects on course grade while controlling for other variables. Finally, results show that when students have more adaptive self-efficacy, specifically in mathematics, impacts of family-based academic risk factors on achievement are lessened or positively strengthened. Virtual school teachers and administrators should consider ways to strengthen students’ self-efficacy and build programs to teach students about important study habits, such as time management.